Inclusive gaming through AI: a perspective for identifying opportunities and obstacles through co-design with people living with MND - Dwyer, Natasha; Harrison, Matthew; O’Mara, Ben; Harley, Kirsten (Frontiers in Computer Science, 2024)
This interdisciplinary research initiative seeks to enhance the accessibility of video gaming for individuals living with Motor Neurone Disease (MND), a condition characterized by progressive muscle weakness. Gaming serves as a social and recreational outlet for many, connecting friends, family, and even strangers through collaboration and competition. However, MND’s disease progression, including muscle weakness and paralysis, severely limit the ability to engage in gaming. In this paper, we desscribe our exploration of AI solutions to improve accessibility to gaming. We argue that any application of accessible AI must be led by lived experience. Notably, we found in our previous scoping review, existing academic research into video games for those living with MND largely neglects the experiences of MND patients in the context of video games and AI, which was a prompt for us to address this critical gap.